Estimating Surface Water Presence and Infiltration in Ephemeral to Intermittent Streams in the Southwestern US - Gallo, Erika L.; Meixner, Thomas; Lohse, Kathleen A.; Nicholas, Hillary (Frontiers in Water, 2020)
Streamflow in arid and semi-arid regions is predominantly temporary, an integral part of mountain block hydrology and of significant importance for groundwater recharge and biogeochemical processes. However, temporary streamflow regimes remain poorly quantified. We use electrical resistance sensors and USGS stream gauge data to quantify streamflow intermittency as streamflow presence and water presence, which includes streamflow, ponding and soil moisture, in 15 southern Arizona streams spanning a climate gradient (mean annual precipitation from 160 to 750 mm). We use stream channel sediment data to estimate saturated hydraulic conductivity and potential annual infiltration. Annual streamflow ranged 0.6 to 82.4% or 2 to 301 days; while water presence ranged from 2.6 to 82.4% or 10 to over 301 days, or 4 to 33 times longer than streamflow. We identified 5 statistically distinct flow regimes based on the annual percent streamflow and water presence: 1) dry-ephemeral, 2) wet-ephemeral, 3) dry-intermittent, 4) wet-intermittent and 5) seasonally-intermittent. In contrast to our expectations, stream channel density was a better predictor of streamflow and water presence than rainfall alone. Whereas the dry-ephemeral and wet-ephemeral flow regimes varied with seasonal precipitation, the dry-intermittent, wet intermittent and seasonally-intermittent flow regimes did not. These results coupled with the potential infiltration estimates indicate that streamflow at the driest sites occurs in response to rainfall and overland flow while groundwater discharge and vadose zone contributions enhance streamflow at the wetter sites. We suggest that on a short temporal scale, and with respect to water presence, wetter sites might be buffered better against shifts in the timing and distribution of precipitation in response to climate change. Flow regime classifications that include both stream flow and water presence, rather than on stream flow alone, may be important for predicting thresholds in ecological functions and refugia in these dryland systems.